2020
DOI: 10.1007/s42729-020-00255-5
|View full text |Cite
|
Sign up to set email alerts
|

Warming Change Nutritional Status and Improve Stylosanthes capitata Vogel Growth Only Under Well-Watered Conditions

Abstract: Climate change may impact plant nutritional status and productivity. However, few studies evaluate the effects of global change variables on tropical forage species under field conditions. In this study, we evaluated the isolated and combined effects of warming and drought on nutritional status and its relations with net photosynthesis rate and aboveground dry mass production of Stylosanthes capitata, a C 3 tropical forage legume under field conditions. We tested two canopy temperature levels, ambient (Ta) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, under field conditions crops are usually subjected to different abiotic stress simultaneously. Recent studies revealed that the responses of forage tropical plants to a combination of different abiotic stresses, such as warming and drought, are unique and cannot be extrapolated from simply studying each of these different stresses applied individually (Barreto et al., 2020; Borjas‐Ventura et al., 2019; Habermann, et al., 2019; Olivera‐Viciedo et al., 2019). Therefore, field and multi‐factor experimental approaches are needed to improve our understanding of plant nutrient dynamics under future climate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, under field conditions crops are usually subjected to different abiotic stress simultaneously. Recent studies revealed that the responses of forage tropical plants to a combination of different abiotic stresses, such as warming and drought, are unique and cannot be extrapolated from simply studying each of these different stresses applied individually (Barreto et al., 2020; Borjas‐Ventura et al., 2019; Habermann, et al., 2019; Olivera‐Viciedo et al., 2019). Therefore, field and multi‐factor experimental approaches are needed to improve our understanding of plant nutrient dynamics under future climate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Climatic warming could have positive [ 52 ], neutral [ 53 ], and negative [ 17 , 54 ] impacts on plant nutrition status, which strongly depend on water status (e.g., [ 17 , 53 ]) and ecosystem/biome types [ 52 , 54 , 55 ]. The present results showed no warming effect on N mass across all dominant species (Table 1 ), indicating a neutral effect [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Climatic warming could have positive [ 52 ], neutral [ 53 ], and negative [ 17 , 54 ] impacts on plant nutrition status, which strongly depend on water status (e.g., [ 17 , 53 ]) and ecosystem/biome types [ 52 , 54 , 55 ]. The present results showed no warming effect on N mass across all dominant species (Table 1 ), indicating a neutral effect [ 53 ]. Warming may reduce the N concentration due to dilution under amply watered conditions; however, warming with drought may cancel the dilution due to inhibited plant growth [ 14 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It`s widely known that plants responses and vulnerabilities to concomitant abiotic stresses cannot be directly extrapolated from studies that evaluate each stress individually, since interactive effects are at play under eld conditions (Barreto et al, 2020;Habermann et al, 2021;Olivera-Viciedo et al, 2019, 2021b. This presupposes that the response of plants in adverse situations is dependent (at least in part) on their adaptation and tolerance to combined stress conditions.…”
Section: Introductionmentioning
confidence: 99%